Numerical study of the impact of climate change on the yield of wheat, soybean and maize - Streck, Nereu Augusto; Alberto, Cleber Maus (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate through a numerical study the impact of a possible climate change on the yield of wheat, soybean and maize, in Santa Maria, RS. Climate change scenarios were created by doubling CO2, with different increases in air temperature, and with increases and without increases in rainfall. Yield of the three crops was simulated with models available in the literature. It was concluded that projected climate change will affect wheat, soybean and maize yield in Santa Maria, RS, Brazil. The increase of 2, 3 and 6ºC may cancel the benefits of increasing CO2 on yield of wheat, soybean and maize, respectively.